2020
DOI: 10.1186/s13052-020-00857-w
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence during pregnancy and risk of still birth in hospitals of Tigray region Ethiopia

Abstract: Background: Pregnancy may represent a time of exceptional vulnerability to intimate partner violence because of changes in women's conditions. Despite the fact that intimate partner violence during pregnancy confers considerable risk to the health of the woman and her fetus, data regarding to association of stillbirth and intimate partner violence is lacking in Tigray region. The objective of this study is to assess intimate partner violence during pregnancy and its association with still birth among postpartu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
8
2
2
Order By: Relevance
“…For instance, we excluded women with a recent history of stillbirth, which is a known risk factor for subsequent stillbirth [ 9 ]. On the other side, the rate in our study was also lower than reports from health facility-based studies elsewhere in Ethiopia; 92 in Yirgalem [ 10 ], 36.8 in Axum [ 13 ], 71 in Gondar [ 21 ], 80 in Jimma [ 45 ], 36 in Tigray [ 46 ] per 1000 births. It was also lower than those from Tanzania, 35 [ 2 ] and Ghana, 34 [ 19 ] per 1000 births.…”
Section: Discussioncontrasting
confidence: 85%
“…For instance, we excluded women with a recent history of stillbirth, which is a known risk factor for subsequent stillbirth [ 9 ]. On the other side, the rate in our study was also lower than reports from health facility-based studies elsewhere in Ethiopia; 92 in Yirgalem [ 10 ], 36.8 in Axum [ 13 ], 71 in Gondar [ 21 ], 80 in Jimma [ 45 ], 36 in Tigray [ 46 ] per 1000 births. It was also lower than those from Tanzania, 35 [ 2 ] and Ghana, 34 [ 19 ] per 1000 births.…”
Section: Discussioncontrasting
confidence: 85%
“…Differences in prevalence found by different authors in the same country is not readily appreciated in the prevalence maps. For the same country, taking Ethiopia as an example, Gebrezgi et al, provided a prevalence of any type of IPV of 98% in the Tigrai (43) area, whereas Gebreslasie et al, showed a prevalence of 7.3% (44). In another example in Kenya, the 67% prevalence of any type of violence reported by Owaka et al (45), was almost duplicate of the 37% rate provided by Makayoto et al (46).…”
Section: Discussionmentioning
confidence: 93%
“…The review was conducted among 20 109 live births delivered after 28 weeks of gestation to estimate the pooled effect of preterm birth on adverse outcomes. Of those, 8 studies reported perinatal mortality, 24 , 25 , 49 52 3 studies 53 55 reported stillbirth, 9 studies 27 , 56 63 reported neonatal sepsis, 4 studies 26 , 64 – 66 were on neonatal hypothermia and 8 studies 28 , 67 74 reported neonatal mortality. Regarding the design of the included studies, sixteen (48.5%) were cross-sectional studies, 26 , 49 , 51 , 53 , 56 , 58 , 60 , 64 , 66 , 68 , 72 74 8 (24.2%) studies were case-control 24 , 25 , 50 , 52 , 54 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the design of the included studies, sixteen (48.5%) were cross-sectional studies, 26 , 49 , 51 , 53 , 56 , 58 , 60 , 64 , 66 , 68 , 72 74 8 (24.2%) studies were case-control 24 , 25 , 50 , 52 , 54 , 59 , 60 , 65 and 7 (21.2%)were cohort studies. 28 , 55 , 67 , 69 , 71 , 73 The articles were published between 2014 and 2020. To estimate neonatal mortality, the largest sample size was 3463 live births in a prospective follow-up study conducted in Oromia region 73 followed by 1770 sample size in a study conducted in Tigray.…”
Section: Resultsmentioning
confidence: 99%